Environmental enrichment mitigates PTSD-like behaviors in adult male rats exposed to early life stress by regulating histone acetylation in the hippocampus and amygdala. (November 2022) - Xu, Hanfang; Li, Bozhi; Li, Ling; Fan, Zhixin; Gong, Xiayu; Wu, Lili; Yan, Can
Abstract: Early life stress (ELS) can cause long-term changes in gene expression, affect cognition, mood, and behavior, and increase susceptibility to post-traumatic stress disorder (PTSD) in adulthood, in which the histone acetylation plays a crucial role. Studies have found that environmental enrichment (EE) mitigated the unfavorable outcomes of ELS. However, the underlying mechanism of the histone acetylation is not yet completely clear. The purpose of this study was to explore the effect of EE on the histone acetylation after ELS. In this study, using single prolonged stress (SPS) paradigm in early adolescent rats explored the long-term effects of ELS on behavior, the activity of histone acetyltransferases (HATs) and histone deacetylases (HDACs), as well as the acetylation levels of the lysine 9 site of histone H3 (H3K9) and lysine 12 site of histone H4 (H4K12) in the hippocampus and amygdala. Meanwhile, the protective effects of EE intervention were examined. We found that adult male rats exposed to ELS showed behavioral changes, including reduced locomotor activity, increased anxiety-like behaviors, impaired spatial learning and memory, enhanced contextual and cued fear memory, and the HATs/HDACs ratio and acetyl H3K9 (Ac–H3K9) and acetyl H4K12 (Ac–H4K12) were increased in the hippocampus and decreased in the amygdala. Furthermore, EE attenuated the behavioral abnormalities from ELS, possibly through down-regulating the activity of HATs in the hippocampus and up-regulating HDACs activities in the amygdala. These finding suggested that EE could ameliorate ELS-induced PTSD-like behaviors by regulating histone acetylation in the hippocampus and amygdala, reducing the susceptibility to PTSD in adulthood.